2016
DOI: 10.1026/0049-8637/a000140
|View full text |Cite
|
Sign up to set email alerts
|

Haben Schüler mit optimistischen Selbsteinschätzungen die Nase vorn?

Abstract: Zusammenfassung. In der pädagogisch-psychologischen Selbstkonzeptliteratur findet sich vielfach die Forderung nach optimistischen Fähigkeitsselbstkonzepten. Längsschnittstudien, die dezidiert den Auswirkungen von Selbstüber- und -unterschätzungen auf die Leistungsentwicklung nachgehen, existieren bislang jedoch kaum. In der vorliegenden Studie wurde mittels Residualscores das Ausmaß an Selbstüber- und -unterschätzungen in Bezug auf das Fach Mathematik von 925 Erstklässler/-innen bestimmt und über Cross-Lagged-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
11
0
3
Order By: Relevance
“…Interestingly, higher self-concept led to too high judgments. Still, we do not know whether the reported self-concepts were realistic or rather optimistic (Praetorius et al 2016). Overoptimistic self-concepts or self-enhancement tendencies might be responsible for the effect of self-concept on overconfidence (Alicke and Sedikides 2009;Guay et al 2010;Jiang and Kleitman 2015;Krueger 2016;Marsh and Craven 2006;Marsh and Martin 2011).…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, higher self-concept led to too high judgments. Still, we do not know whether the reported self-concepts were realistic or rather optimistic (Praetorius et al 2016). Overoptimistic self-concepts or self-enhancement tendencies might be responsible for the effect of self-concept on overconfidence (Alicke and Sedikides 2009;Guay et al 2010;Jiang and Kleitman 2015;Krueger 2016;Marsh and Craven 2006;Marsh and Martin 2011).…”
Section: Discussionmentioning
confidence: 89%
“…According to Herppich et al ( 2018 ), differences in the judgment accuracy of teachers can be explained by qualitatively different ways in which they carry out the assessment process (e.g., in the way they notice and process information, form hypotheses, or collect information). Differences in learner characteristics can affect all these processes, leading, for example, those in the motivated profile to carry out relevant learning activities in the assessment process in a somewhat more superficial way (Praetorius et al, 2016 ). The lack of knowledge and motivation of those in the potentially struggling profile should also become evident during the assessment process (Stürmer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-regulation skills have been shown to be highly relevant for learning in many educational contexts and are also expected to play an important role in pre-service teachers’ acquisition of complex skills (Dent & Koenka, 2016 ; Kara et al, 2021 ). Self-efficacy has also repeatedly been shown to be an important capacity for learning in general (Dupeyrat et al, 2011 ; Praetorius et al, 2016 ). Some studies have also highlighted its relevance to teaching (Tschannen-Moran et al, 1998 ); however, other studies, such as Klug et al’s ( 2016 ) study, have shown no relevant relationship between self-efficacy and teachers’ assessment skills.…”
Section: Introductionmentioning
confidence: 99%
“…Folglich kann starke Messinvarianz angenommen werden (Meade, Johnson, & Braddy, 2008;Widaman & Thompson, 2003). (Helmke & van Aken, 1995;Praetorius, et al, 2016;Skaalvika & Valås, 1999) (Harter, 1999). Gerade der zunehmende Zusammenhang zwischen Selbstkonzept und Leistung in der Grundschule wird als ein Indiz dafür betrachtet, dass sich das Selbstkonzept langsam den tatsächlichen Leistungen anpasst.…”
Section: Statistische Analysenunclassified